2020
DOI: 10.1136/emermed-2019-208951
|View full text |Cite
|
Sign up to set email alerts
|

Peek at the glass ceiling: gender distribution of leadership among emergency medicine residency programs

Abstract: BackgroundA gender gap in faculty rank at academic institutions exists; however, data among graduate medical education (GME) programmes are limited. There is a need to assess gender disparities in GME leadership, as a lack of female leadership may affect recruitment, role modelling and mentorship of female trainees. This cross-sectional study aimed to describe the current state of gender in programme leadership (department chair, programme director (PD), associate/assistant PD (APD) and clerkship director (CD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…While women are underrepresented in executive leadership positions, education leadership roles did have a significantly greater representation of women compared to other leadership roles. This is similar to previous findings in the literature 21,22 . Future work should investigate education positions to learn if anything about these roles, systems, and/or processes can be used to increase the number of women in other leadership positions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While women are underrepresented in executive leadership positions, education leadership roles did have a significantly greater representation of women compared to other leadership roles. This is similar to previous findings in the literature 21,22 . Future work should investigate education positions to learn if anything about these roles, systems, and/or processes can be used to increase the number of women in other leadership positions.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to previous findings in the literature. 21,22 Future work should investigate education positions to learn if anything about these roles, systems, and/or processes can be used to increase the number of women in other leadership positions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that female emergency physicians hold the role of assistant PD at a higher-than-anticipated rate compared with the current number of women in EM but in proportion to the current number of female EM residents. 8 Because the assistant PD positions are often filled by early-career emergency physicians, this may explain why these figures more closely mirror the percentage of women in EM training.…”
Section: Discussionmentioning
confidence: 99%
“…7 As of the 2018 to 2019 academic year, female faculty comprised 11.2% of chairs, 34.6% of program directors (PDs), 40.5% of associate/assistant PDs, and 46.5% of clerkship directors in U.S. EM residency programs. 8 In addition to EM faculty, prior studies have examined EM resident and chief resident gender distribution.…”
mentioning
confidence: 99%
“…42,62,63 Over a 10-year period, the probabilities of promotion were lower and probabilities of attrition were higher for UIM faculty and women. 41 UIM physicians are less likely to hold administrative leadership positions in various departments, 3,[64][65][66] serve as program directors, 67,68 receive NIH research awards, 3 grants, 26 and receive tenure 69 than their non-UIM peers. Even after adjusting for tenure status, degree, gender, and NIH award status, UIM Table 4.…”
Section: Leadership and Academic Advancementmentioning
confidence: 99%